Computer ethics training in higher educational institutions as one of the factofs of forming the social responsibility of future specialists - Lapuzina, Olena Mykolayivna (Національний технічний університет "Харківський політехнічний інститут", 2022)
The given article encompasses problems of computer ethics role in the technical specialists preparing process. The attention is focused on an urgency and practical significance of this problem in modern conditions of computer technique development. The article examines the special role of higher education in creating computer ethics standards, analyzes the study of modern forms of information ethics, which is extremely relevant in the conditions of global digitalization, as well as at the justification of the need for its study in institutions of higher education. The skills and abilities of technical students and students who study in the field of informatics and plan to be future software developers responsible for making decisions about various types of technology development are considered in the article. A conclusion was made about the need to introduce a course on the ethics of the global information space, that is, computer ethics, into the education of students, along with the creation and implementation of codes of scientific information ethics for scientists and teachers of modern universities.

Стаття присвячена аналізу питань ролі комп’ютерної етики при підготовці фахівців технічного напрямку у закладах вищої освіти. Увага акцентується на актуальності та практичної важливості цієї проблеми в сучасних умовах розвитку інформаційних технологій. У статті розглядається особлива роль вищої освіти у створенні стандартів комп’ютерної етики. Стаття націлена на вивчення сучасних форм інформаційної етики, яка є конче актуальною в умовах глобальної діджиталізації, а також на обґрунтування необхідності її вивчення у технічних університетах. Метою статті є загальний аналіз вмінь та навичок студентів технічного напряму навчання та студентів, які навчаються в галузі інформатики і планують бути майбутніми розробниками програмного забезпечення, відповідальними за прийняття рішень щодо різних типів розвитку технологій. Зроблено висновок про необхідність впровадження курсу етики глобального інформаційного простору, тобто комп’ютерної етики, у навчання студентів, поряд зі створенням та впровадженням кодексів наукової інформаційної етики для науковців та викладачів сучасних вишів.
Викладання комп'ютерної етики у закладах вищої освіти як один із чинників формування соціальної відповідальності майбутніх фахівців
Keywords: computer ethics; information technologies; students; technical direction of study; code of computer ethics; комп'ютерна етика; інформаційні технології; студенти; технічний напрям навчання; кодекс комп'ютерної етики